DETECTION AND IDENTIFICATION OF NEMATODE WORM EGGS IN LAYING HENS AT HASNA FARM, WAJO REGENCY AND ANDI MUKTI FARM, PINRANG REGENCY, SOUTH SULAWESI - Anggi Aprianti; Lilis Juniarti; Andi Magfira Satya Apada; Muh. Danawir Alwi; Zainal Abidin Kholilullah; Zulfikri Mustakdir; Fedri Rell (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Laying chickens are a type of poultry that has the potential to produce quite large eggs in Indonesia. One of the pathogens that often attacks laying hens is nematode worms which can cause economic losses for farmers. This research aims to detect and identify the presence of nematode worm eggs that infect laying hens on the Hasna farm, Wajo Regency and the Andi Mukti farm, Pinrang Regency. The research was carried out at the Maros Veterinary Center Laboratory and the Integrated Veterinary Laboratory at Hasanuddin University. The samples used in this research were 48 feces taken from each farm from laying hens. Samples were examined using three test methods, namely native test, floating method and sedimentation method. The results obtained were that on Hasna's farm there were 7 individuals that were detected positive for nematodes, of which there were 3 types of worm eggs, namely Ascaridia galli, Heterakis gallinarum and Strongyloides sp and 12 animals on the Andi Mukti farm were detected positive for nematodes, where there were 2 types of worm eggs, namely Ascaridia galli and Heterakis gallinarum. Based on this research, there was nematode worm infection on Hasna and Andi Mukti's farms.